Bioactive peptides applications for improving nutrition and health - Owusu-Apenten, R. K. (CRC Press, 2010)
"Presenting data from human studies and trials, along with recent research findings, this work summarizes the applications, and benefits of bioactive peptides used to mitigate major metabolic derangements arising from chronic illnesses and resulting in unwanted weight loss. Recent studies show bioactive peptides to enhance the body's antioxidant status, antisepsis capacity, immune function, anti-inflammatory capacity, mineral absorption, and appetite. This book covers general principles, such as host response, quality factors, protein economics, and muscle loss. It includes case studies on ageing, AIDS, COPD, diabetes, inflammatory bowel disease, kidney failure, and tuberculosis."--Provided by publisher.
Keywords: Peptide drugs.; Dietary supplements.; Proteins -- Metabolism.; Proteins in human nutrition.; Appetite stimulants.; elektronické knihy; electronic books